Guiding transition metal-doped hollow cerium tandem nanozymes with elaborately regulated multi-enzymatic activities for intensive chemodynamic therapy - Dong, Shuming (2022)
Clinical applications of nanozyme-initiated chemodynamic therapy (NCDT) have been severely limited by poor catalytic efficiency of nanozymes, insufficient endogenous H2O2 content, and off-target consumption. Herein, we develop hollow mesoporous Mn/Zr-co-doped CeO2 tandem nanozyme (PHMZCO-AT) with elaborately regulated multi-enzymatic activities, i.e., simultaneously enhancing superoxide dismutase (SOD)-like and peroxidase (POD)-like activities and inhibiting catalase (CAT)-like activity, serving as an H2O2 homeostasis disruptor to promote H2O2 evolvement and restrain off-target elimination of H2O2 for achieving intensive NCDT. PHMZCO-AT nanozymes with SOD-like activity can catalyze endogenous O2·– into H2O2 in the tumor region. The suppression of CAT activity and depletion of glutathione by PHMZCO-AT largely weaken the off-target decomposition of H2O2 to H2O. Elevated H2O2 is then exclusively catalyzed by the downstream POD-like activity of PHMZCO-AT to generate toxic hydroxyl radicals, further inducing tumor apoptosis and death. T1-weighted magnetic resonance imaging and high-contrast X-ray computed tomography imaging are also achieved using PEG/PHMZCO-AT nanozymes due to the existence of paramagnetic Mn2+ species and high X-ray attenuation ability of elemental Zr, permitting in vivo tracking of the therapeutic process. This work presents a powerful paradigm to achieve intensive NCDT efficacy by simultaneously regulating multi-enzymatic activities of Ce-based nanozymes and perturbing the H2O2 homeostasis in tumor microenvironment.